2017
DOI: 10.1155/2017/5790102
|View full text |Cite
|
Sign up to set email alerts
|

Acute Acalculous Cholecystitis: A Rare Presentation of Primary Epstein-Barr Virus Infection in Adults—Case Report and Review of the Literature

Abstract: Primary Epstein-Barr virus (EBV) infection is almost always a self-limited disease characterized by sore throat, fever, and lymphadenopathy. Hepatic involvement is usually characterized by mild elevations of aminotransferases and resolves spontaneously. Although isolated gallbladder wall thickness has been reported in these patients, acute acalculous cholecystitis is an atypical presentation of primary EBV infection. We presented a young women admitted with a 10-day history of fever, nausea, malaise who had ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Clinical presentation, laboratory and imaging findings, and complications and outcomes of EBV-related AAC have been reviewed extensively in the past in a couple of reviews [23,30]. Abdominal pain remains the most common symptom.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical presentation, laboratory and imaging findings, and complications and outcomes of EBV-related AAC have been reviewed extensively in the past in a couple of reviews [23,30]. Abdominal pain remains the most common symptom.…”
Section: Resultsmentioning
confidence: 99%
“…9,12 Once the diagnosis of EBV is made, further workup is generally not warranted. 1,2 Treatment of uncomplicated infectious mononucleosis usually requires only symptomatic treatment with antipyretics, hydration, and rest. 1,2,6 Often patients may experience abdominal pain, which may in part be due to splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Treatment of uncomplicated infectious mononucleosis usually requires only symptomatic treatment with antipyretics, hydration, and rest. 1,2,6 Often patients may experience abdominal pain, which may in part be due to splenomegaly. 6 If splenomegaly is present, it is prudent to warn the patient against Clinical Practice and Cases in Emergency Medicine Herold et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cases recovered conservatively without surgery or corticosteroids [7]. Upon a literature review, at least 12 cases of AAC caused by EBV have been reported since the year 2016 [4,[8][9][10][11][12][13][14][15][16][17][18]. Eight patients were females and four patients were males.…”
Section: Discussionmentioning
confidence: 99%